Role of electroencephalogram and oxygen saturation in the induction mechanism of arousal for obstructive sleep apnea-hypopnea syndrome patients. Issue 4 (3rd July 2016) - Yan, Jia; Zhang, Xiangmin; Yen, Chen-Wen; Sun, Lin; Yu, Enjia; Luo, Yuxi
Abstract: Arousal concomitant with obstructive sleep apnea-hypopnea syndrome (OSAHS) is known to result in sleep fragmentation and excessive daytime sleepiness. The cause of arousal is multifarious, and the mechanism is not yet clear. The aim of this study was to further research the induction mechanism of arousal by investigating the variation of electroencephalogram (EEG) and oxygen saturation (SaO2 ). This study enrolled 20 subjects with a clinical diagnosis of OSAHS who underwent overnight polysomnography. Respiratory events and arousals were scored, and individuals with insufficient samples (<30) were excluded. Thus, 13 subjects mostly with severe OSAHS were analyzed in this study. The wavelet coefficients, spectral power of EEG (C4-M1 and C3-M2) before arousal or airway reopening, and the maximum desaturations of SaO2 during respiratory events were analyzed. For most subjects, EEG (in stages N1 and N2) during respiratory events with arousals exhibited significantly lower values of wavelet coefficients and spectral power ( p < 0.05). The maximum desaturations of SaO2 during respiratory events with arousals are larger than those without among individual. In binary logistic regression analysis, the P values of EEG features and SaO2 desaturation were both less than 0.001. Our results demonstrate that in light NREM stage, less activity in EEG during respiratory events and larger SaO2 drop both independently were related to the occurrence of arousal. These significant differences come from major subjects based on the statistical analysis, and help supplement the induction mechanism of arousal.